2014
DOI: 10.3748/wjg.v20.i24.7785
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound in the diagnosis of pancreatic intraductal papillary mucinous neoplasms

Abstract: Pancreatic cystic lesions are increasingly recognised due to the widespread use of different imaging modalities. Intraductal papillary mucinous neoplasms (IPMNs) of the pancreas represent a common, but also heterogeneous group of cystic tumors with a significant malignant potential. These neoplasms must be differentiated from other cystic tumors and properly classified into their different types, main-duct IPMNs vs branch-duct IPMNs. These types have a different malignant potential and therefore, different tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Endoscopic ultrasound and analysis of pancreatic cyst fluid obtained by EUS‐guided FNA have been reported to be highly diagnostic , but these results are operator‐dependent . In addition, this procedure is invasive, expensive and difficult to apply to every patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopic ultrasound and analysis of pancreatic cyst fluid obtained by EUS‐guided FNA have been reported to be highly diagnostic , but these results are operator‐dependent . In addition, this procedure is invasive, expensive and difficult to apply to every patient.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other analysis [14] reported that cyst size greater than 3 cm had the strongest association with malignant IPMN, followed by presence of mural nodules and MPD dilatation, suggesting that the diagnostic power of each imaging finding may vary. Another recent study [15] reported that the presence of mural nodules had Endoscopic ultrasound and analysis of pancreatic cyst fluid obtained by EUS-guided FNA have been reported to be highly diagnostic [7,9,16], but these results are operator-dependent [10]. In addition, this procedure is invasive, expensive and difficult to apply to every patient.…”
Section: Discussionmentioning
confidence: 99%
“…Studies reveal that both CT and magnetic resonance imaging have equal accuracy in staging malignancy of pancreatic ductal neoplasms [6,8], Magnetic resonance cholangiopancreatography (MRCP) appears to have more sensitivity than ERCP to demonstrate internal septations and multiple focal cysts according to International Consensus Guidelines 2012 [8], it is also recommended to be used in the follow-up. Also, endoscopic ultrasound (EUS) elastography and confocal laser endomicroscopy are new methods to diagnose IPMNs but need further evaluation before putting in use [6,7,9].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, EUS is highly preferable as an imaging method for pancreatic cystic neoplasms as it can distinguish IPMNs anatomical types, and demonstrate features of suspected malignancy, in addition to the ability to perform a guided fine-needle aspiration for further evaluation [9].…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] Furthermore, intraductal ultrasound appears to be useful in differentiating invasive IPMNs from benign lesions but is not routinely used. [ 85 ] A recent study by Lee et al . showed that an EUS scoring system using pancreatic cyst size, height of mural nodules, MD dilation, septal thickening, and patulous orifice was more accurate at predicting malignancy than the Sendai Consensus Guidelines.…”
Section: Diagnosis and Managementmentioning
confidence: 99%